1995
DOI: 10.1007/bf00301758
|View full text |Cite
|
Sign up to set email alerts
|

Subdural intracranial pressure monitoring in craniosynostosis: its role in surgical management

Abstract: In the management of craniosynostosis subdural intracranial pressure (ICP) monitoring has proved a useful and safe means of identifying those children with raised ICP who are at risk from its long-term sequelae and who would benefit from early surgical intervention. Overnight subdural ICP recordings have been obtained in 136 unoperated cases of craniosynostosis. Fifteen patients were studied both before and after cranial vault remodelling procedures. ICP was raised (> 15 mmHg) in 35%, borderline (10-15 mmHg) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
115
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 158 publications
(118 citation statements)
references
References 21 publications
2
115
0
1
Order By: Relevance
“…This incidence is still greater than that observed in other series of nonoperated scaphocephalic patients. 4,6,22,40,41,49,50 This difference may be explained by either the greater age of our patients or the high proportion of mild and nonscaphocephalic patients in the group.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…This incidence is still greater than that observed in other series of nonoperated scaphocephalic patients. 4,6,22,40,41,49,50 This difference may be explained by either the greater age of our patients or the high proportion of mild and nonscaphocephalic patients in the group.…”
Section: Discussionmentioning
confidence: 82%
“…Furthermore, it is now recognized that raised intracranial pressure (ICP) occurs in this group of patients, with an estimated preoperative incidence between 4.5% and 24%. 6,22,40,41,49,50 Therefore, the treatment of possible preexisting raised ICP, or the prevention of future ICP, provides a clear functional indication for surgery, in addition to the need to correct the morphological deformity present in these children.…”
mentioning
confidence: 99%
“…Our use of a threshold of more than 15 mm Hg to define an abnormally elevated ICP is consistent with that used by all previous studies that have undertaken overnight intracranial ICP monitoring in craniosynostosis, no matter whether an extradural or subdural device was employed. 6,11,13,28,35,42,43,45,46 The pathological significance of multiple B-type waves is also well recognized in the literature. 11,35,50 Consistent with the patient series of van Veelan et al and Cetas et al, we found that elevated ICP was diagnosed late, at least 2 years after primary surgery, with a mean at just under 4.5 years of follow-up.…”
Section: Discussionmentioning
confidence: 96%
“…In the early part of the study period, invasive ICP monitoring (ICPM) was routinely performed at presentation. However, since the late 1990s, we have increasingly relied on deterioration in EDTs (in particular, pattern reversal visual evoked potentials) as an indirect measure of raised ICP, 16,17,33 reserving ICPM for quantitative confirmation when required. When performed, ICPM was continued for 48 hours and results were categorized according to the range proposed by Renier et al 23 (< 10 mm Hg, normal; 10-15 mm Hg, borderline; and > 15 mm Hg, raised), with the addition of plateau waves if they more than doubled the baseline measurement and were sustained for ≥ 20 minutes.…”
Section: Methodsmentioning
confidence: 99%